The Portrayal of Economic and Political Aspects of the Great Depression in America Through Steinbeck’s The Grapes of Wrath - Ikram Amroune, Wafa Baali (My University, 2018)
Abstract The Grapes of Wrath is John Steinbeck’s masterpiece that has proven its magnificence throughout the history of American literature. It is the authentic story of the Oklahoman families who had been evicted from their land and become migrant farmers in California. Thus, they experienced oppression by both the bourgeois and the government. This research requires the use of the Analytical Descriptive approach with the New Historicism theory since it shows the economic conditions that were reflected on many working class Americans during the Great Depression. Besides, it demonstrates how the American political system is reflected on characterization, plot, and symbols in the novel. The Grapes of Wrath is proved to be served as a mean that accurately depicted the Economic and Political aspects of the Great Depression in America.
Keywords: Great Depression, The Grapes of Wrath, Political Aspect, Economic Aspect